Overview of Digital Literacy in Parents with Children Who Have Online Resilience - Dzakiah, Laubna; Wulandari, Primatia Yogi; Cahyono, Rudy (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The digital revolution has attracted digitally native children to become more actively involved as users. The role of parents in this context is crucial to assist children in facing and countering the various risks encountered in this digital world. Children, however, are vulnerable to psychological problems that may arise if digital risks are not properly anticipated. Several research papers prove that mentoring and assistance can help children to develop higher digital resilience. The main prerequisite for effective and proper assistance to children is a strong foundation of digital literacy. The study serves to provide an overview of digital literacy in parents with children who exhibit online resilience. This study employs a qualitative approach primarily using case studies. Data analysis was conducted using an interactive model technique. Research participants were gradually selected using a Google Form in an online selection process, aimed at parents with one or more children aged 6-12 years. Five participants were selected to become the subjects of this study. Data was collected through online interviews. The findings of this study indicate the strength of parent’s digital literacy in each aspect of skills. Characteristics of basic literacy skills influence the practice of mediation to children’s digital activity.Revolusi dunia digital telah menarik anak-anak digital native untuk terlibat semakin aktif sebagai penggunanya. Peran orangtua dalam kondisi ini menjadi krusial untuk mendampingi anak menghadapi dan menangkal pelbagai risiko yang ditemui di dunia digital. Anak-anak bagaimanapun memiliki kerentanan terhadap persoalan psikologis yang setiap saat dapat muncul apabila risiko digital tidak diantisipasi dengan baik. Beberapa publikasi penelitian membuktikan bahwa pendampingan yang tepat dapat membantu anak-anak mengembangkan resiliensi daring yang lebih tinggi. Syarat utama untuk melakukan pendampingan yang tepat pada anak adalah penguasaan literasi digital yang baik. Terkait hal itu, penelitian ini bertujuan untuk memberikan gambaran tentang literasi digital yang dimiliki orang tua dengan anak yang memiliki resiliensi daring. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Analisis data dilakukan dengan teknik model interaktif. Partisipan penelitian diperoleh secara bertahap melalui proses seleksi daring dengan Google Form kepada orangtua yang memiliki anak berusia 6-12 tahun dan diperoleh 5 partisipan yang menjadi subjek utama penelitian ini. Hasil penelitian menunjukkan kekuatan literasi digital orang tua pada masing-masing aspek keterampilan literasi digital. Karakteristik literasi digital orang tua memengaruhi strategi pendampingan aktivitas digital anak.